Limiting the Use of Cash for Big Purchases: Assessing the Case for Uniform Cash Thresholds - Peter Sands; Benjamin Weisman; Haylea Campbell; Tom Keatinge (Deutsche Bundesbank, 2017)
For all the hype about electronic payment systems, cash remains by far the world's most popular mechanism. However, over the past year we have seen an intensification of the discussion about the role of cash in society. Cash has great advantages: it is familiar, simple to use and ubiquitously accepted. However, cash also has downsides. Because cash transactions leave no record, cash plays a critical role in money laundering, tax evasion and terrorist financing. This debate generates strong feelings, to the extent that it is sometimes depicted as a “war on cash”. Some decry moves to curtail cash usage as an unwarranted encroachment on individual liberty and a manifestation of an over-reaching state. Others see physical cash as a costly remnant of a pre-digital age that we should get rid of as soon as is feasible. Yet it is also possible to hold a position between these extremes: acknowledging the continued value of cash in modern society, whilst seeking ways to curb its misuse. In 2016 we witnessed a number of policy initiatives aimed at curbing the illicit use of cash. For example, the ECB decided to stop issuing the exteuro500 note due to concerns about its role in illicit finance. India implemented a radical “demonetisation” strategy, abolishing the 500 and 1000 rupee notes in an effort to tackle the scourge of “black money”. Various governments promoted innovative digital payments systems to replace cash, accelerate financial inclusion and reduce benefit fraud...
Keywords: 330